Evaluation of Teaching Materials For Mind Mapping-Based Islamic Religious Education Curriculum Review: Implications For the Practicality of Learning - Suarni, Suarni; Mustami, Muh. Khalifah; Ibrahim, Misykat Malik; Kasim, Amrah; Azizah, St; Saprin, Saprin; Rosdianah, Rosdianah (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to evaluate the practicality of mind mapping-based teaching materials in improving students' understanding and retention of information in the Islamic Religious Education Curriculum Review course at Muhammadiyah Kendari University. This research was conducted amidst various challenges related to traditional teaching methods, time constraints, and students' difficulties in understanding complex concepts. This study used a mixed research design using the sequential explanatory method. Quantitative data was collected through questionnaires given to 103 students, followed by qualitative data collection through interviews and document analysis with teaching lecturers. From the data analysis, it was found that mind-mapping-based teaching materials are very practical in supporting the learning process. As many as 85% of students stated that this teaching material was very helpful in understanding the material taught. Lecturers' responses also showed that this teaching material is practical and can be used in the learning process. These findings indicate the importance of developing innovative and adaptive teaching materials to meet students' learning needs effectively. This study recommends the adoption of mind mapping-based learning models accompanied by organized internal and external support to facilitate the provision of balanced and sustainable knowledge in accordance with modern educational trends and student needs.